PEMANFAATAN HARTA GHANIMAH MENURUT HUKUM ISLAM - Hamdiyah Hamdiyah (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2019)
This research is entitled "Utilization of Ghanimah's AssetsAccording to Islamic Law," in order to examine three issues, namelythe utilization of the Ghanimah property according to its types, the useof Ghanimah on the present and the use of the Ghanimah propertyaccording to Islamic law. The research aims to obtain a clear pictureof the use of the Ghanimah property according to its types, in thepresent and according to Islamic law. This research uses descriptiveanalysis method. The results of his research were obtained, that theproperty was given specifically by priests to members of theMujahideen forces to encourage and encourage them to join in thewar, the utilization and management of Fai 'assets, namely the right ofthe Prophet, so that he may use them according to his will. Themanagement of the treasures of Ghanimah means assets taken fromthe enemy who fight by force and defeat. The principle of thedistribution of the property of Ghanimah is also based on the principleof price distribution of Ghanimah, namely the person who gets onepart, while the person riding the horse gets three parts, the provision isnone other than the additional cost for the horse. riding a horse withhis horse, for Allah (the benefit of the Muslims) and his apostles. forthe Apostle's relatives, for orphans, for poor people for Ibn Sabil(people who were displaced on their way or expelled from theirhomes. Whereas 4/5 parts were reserved for soldiers who fought.